Effects of Hibiscus sabdariffa L. extract on multispecies Porphyromonas gingivalis and Treponema denticola biofilms in vitro - Angela Winson; Trijani Suwandi; Olivia Nauli Komala (Wolters Kluwer Medknow Publications, 2023)
Background: Porphyromonas gingivalis and Treponema denticola are bacteria that play a crucial role in periodontitis. Hibiscus sabdariffa L. contains flavonoids, alkaloids, saponins, and tannins; compounds which are expected to inhibit biofilm formation with minimal side effects. Objectives: To determine the secondary metabolite compounds present in H. sabdariffa L. and its effect on multispecies biofilms formation consisted of P. gingivalis and T. denticola. Methods: This study used H. sabdariffa L. calyx extract with concentrations of 100%, 50%, 25%, 12.5%, 6.25%, 3.125%, and 1.5625%. The positive control used in this study was 0.2% chlorhexidine, and the negative control was brain heart infusion broth. The bacterial biofilm was grown for 1, 6, and 24 hours. Results: Hibiscus sabdariffa L. 1.5625% extracted in a 1-h incubation period, 6.25% extracted in a 6-h incubation period, and 3.25% extracted in a 24-h incubation period are more effective than chlorhexidine 0.2% in inhibiting multispecies P. gingivalis and T. denticola biofilms (P < 0.05). Conclusion: Hibiscus sabdariffa L. calyx extract significantly inhibits multispecies P. gingivalis and T. denticola biofilm with the most effective concentration at 100% at 1-h, 6-h, and 24-h incubation periods. Future studies are needed to test the toxicity of H. sabdariffa L. on cells in the oral cavity.